Application of Information Technology in Education - Armaidi; Rahmat Muliana; Firman (el-Nizami : Jurnal Manajemen Pendidikan, 2024)
The application of information technology in education is an effort to integrate technological devices to improve the quality of learning and the efficiency of education management. Information technology, through hardware, software, internet networks, and digital applications, provides a great opportunity to create education that is more effective, inclusive, and relevant to the needs of the digital era. This article discusses the meaning of information technology implementation, its benefits in improving the quality of learning in schools and the factors that influence the success or failure of its implementation. The main benefits of technology in education include increased accessibility of learning resources, efficiency of educational data management, personalization of learning, development of critical thinking skills, and flexibility in distance learning. However, the successful implementation of technology is influenced by factors such as infrastructure, teacher competence, school policy support, student readiness, parent participation, cost, learning content, school culture and maintenance of technology devices. The results of the discussion emphasize that the implementation of information technology requires collaboration from various parties, ranging from the government, schools, to the community, to ensure its sustainability and success. Thus, the optimal use of technology can support a more effective and competitive transformation of education in the future.